Regular classroom inclusion in elementary schools: Formative assessment practices to foster all pupils’ school progression? - Barthélémy, Véronique (Swiss Journal of Educational Research, 2018)
This contribution is embedded within the field of researches focusing on inclusive teaching practices in elementary regular classrooms. In France, the educational system places special educational needs students either in regular classrooms or in self-contained special education classrooms. However, since 2005, governments encourage school inclusion of BEP pupils, which raises many questions about regular teaching practices. With respect to work showing that teachers using formative assessment better handle student diversity, we study to what extend this type of assessment might foster knowledge acquisition, thanks to the feedbacks r received during oral evaluation sessions and collective task checking sessions. Talks with teachers and pupils’ behaviour observations were analysed. Results clearly show participants’ reactions, interactions and regulations.